2017
DOI: 10.9789/2175-5361.2017.v9i3.614-619
|View full text |Cite
|
Sign up to set email alerts
|

A percepção e formação dos acadêmicos de enfermagem acerca da sexualidade humana Perception and formation of nursing academics regarding human sexuality

Abstract: How to quote this article: Nogueira IS; Rodrigues DMMR; Labegalini CMG; et al. Perception and formation of nursing academics regarding human sexuality. Rev Fund Care Online. 2017 jul/set; 9(3):614-619. DOI: http://dx.doi. org/10. 9789/2175-5361.2017.v9i3.614-619 ABSTRACT Objective: To analyze sexuality from the perspective of students of the nursing course of a public educational institution, listing their theoretical and practical training about this subject. Methods: It is a field research, qualitative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
2
0
1
Order By: Relevance
“…Similarly to what was found in other Brazilian studies (Nogueira et al, 2017;Rezende & Sobral, 2016), which identified a lack of nursing studies and discussions about sexuality both in academic settings and in professional practice, this study revealed accounts of shame and insecurity when it comes to the topic of sexuality. These expressions are explained by a lack of knowledge about the topic, which, in turn, is associated with the limited discussion of this topic in education experiences.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly to what was found in other Brazilian studies (Nogueira et al, 2017;Rezende & Sobral, 2016), which identified a lack of nursing studies and discussions about sexuality both in academic settings and in professional practice, this study revealed accounts of shame and insecurity when it comes to the topic of sexuality. These expressions are explained by a lack of knowledge about the topic, which, in turn, is associated with the limited discussion of this topic in education experiences.…”
Section: Discussionsupporting
confidence: 85%
“…Consequently, instead of acting as facilitators, most professionals disregard the need to intervene. These professionals often act as (iatrogenic) destructive agents due to prejudice, ignorance, and the need to impose values (Nogueira, Rodrigues, Labegalini, Lopes & Baldissera, 2017). The integration of the sexuality topic into the context of nursing care should include the various aspects of the complexity that influences our lives.…”
Section: Introductionmentioning
confidence: 99%
“…4 The biomedical vision of fragmentation of the human, which focuses only on pathologies, is still incorporated into nursing practices, especially in the area of sexuality, and directly interferes, making it difficult to promote health for users when there is difficulty in approaching the subject. 8 Therefore , the lower demand for health services from this public may be associated with discrimination and/or the unpreparedness of professionals to deal with sexual diversity. 9 Therefore, the lack of understanding by the nursing professional category about nonheterosexual sexuality can negatively impact quality and care, allowing the provision of care that does not encompass culturally sensitive care in all life cycles.…”
Section: Introductionmentioning
confidence: 99%
“…recolección de datos ocurrió de abril a septiembre de 2019, a través de entrevistas individuales semiestructuradas9 a partir de la aplicación de un instrumento elaborado por la investigadora, que contenía 11 preguntas orientadoras sobre las relaciones de poder en la carrera de enfermería, además de preguntas para caracterizar a los sujetos de la investigación. Las preguntas de este guión fueron sometidas a adaptación por cuatro jueces externos10 con experiencia y conocimiento en entrevistas y/o sobre formación en educación superior.…”
unclassified